2019
DOI: 10.48550/arxiv.1912.00525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laguerre Ensemble: Correlators, Hurwitz Numbers and Hodge Integrals

Massimo Gisonni,
Tamara Grava,
Giulio Ruzza

Abstract: We consider the Laguerre partition function, and derive explicit generating functions for connected correlators with arbitrary integer powers of traces in terms of products of Hahn polynomials. It was recently proven in [13] that correlators have a topological expansion in terms of weakly or strictly monotone Hurwitz numbers, that can be explicitly computed from our formulae. As a second result we identify the Laguerre partition function with only positive couplings and a special value of the parameter α = −1/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Perhaps our polynomials P µ,d (α ′ ) and k ρ,d (α ′ ) may have some interpretation in terms of such enumeration. In fact, this connection has already been stablished for the α = 1 case in [40]. This topic deserves further study.…”
mentioning
confidence: 68%
“…Perhaps our polynomials P µ,d (α ′ ) and k ρ,d (α ′ ) may have some interpretation in terms of such enumeration. In fact, this connection has already been stablished for the α = 1 case in [40]. This topic deserves further study.…”
mentioning
confidence: 68%
“…Recently the study of moments and joint moments of Hermitian ensembles have attracted considerable interest [10,11,13,24]. Here we give new and self contained formulae for the joint moments of unitary ensembles in terms of characters of the symmetric group.…”
Section: Joint Moments Of Tracesmentioning
confidence: 97%
“…Cunden, Dahlqvist and O'Connell [10] showed that the cumulants of the Laguerre ensemble admit an asymptotic expansion in inverse powers of N of whose coefficients are the Hurwitz numbers. Dubrovin and Yang [13] computed the cumulant generating function for the GUE, while Gisonni, Grava and Ruzza [24] calculated the generating function of the cumulants of the LUE.…”
Section: Introductionmentioning
confidence: 99%
“…Monotone Hurwitz theory has proved to be a useful tool with diverse applications [10,24,36,67,72], and its discovery has sparked a surge of interest in combinatorial deformations of classical Hurwitz numbers [3,4,19,27,28,30,52]. Although the subject has taken on a life of its own, monotone Hurwtz numbers were originally summoned from the void as a weapon with which to attack Conjecture 1.1.…”
Section: Stable Asymptoticsmentioning
confidence: 99%